Die Gattungen Oriopsis, Desdemona, und Augeneriella (Sabellidae, Polychaeta). - Banse, Karl (Videnskabelige Meddelelser fra Dansk naturhistorisk Forening i København, 1957)
[English abstract:] The genus Oriopsis of the subfamily Fabricinae of the Sabellidae is revised, 3 species and one subspecies are new described. 2 new genera, Desdemona with 2 new species, and Augeneriella with one new species, are erected. A key is given for the genera of the thorakogoneate Fabricinae. It is shown that these genera may be divided among an "Oriopsis-group" and a "Fabricia-group", the former of which is the more primitive one; it is close to the basis of Sabellidae. [German abstract:] In der Unterfamilie Fabricinae der Sabellidae wird die Gattung Oriopsis revidiert; 3 Arten und eine Unterart werden neu beschrieben. 2 neue Gattungen, Desdemona mit 2 neuen Arten, und Augeneriella mit einer neuen Art, werden errichtet. Für die Gattungen der thorakogoneaten Fabricinae wird ein Bestimmungsschlüssel gegeben und gezeigt, daß sie sich in eine "Oriopsis-" und eine "Fabricia-Gruppe" gliedern lassen. Die Oriopsis-Gruppe ist die primitivere Gruppe und steht der Basis der SabelIiden nahe.
AnnelidaBase. Journal volume for 1957, and paper ends with a note that reprints were published on 31 December, 1957 ["(Særtrykkene udkommet den 31. december 1957)."].